Financial Performance Analysis at PT. Mandala Multifinance Tbk, which is listed on Indonesia Stock Exchange - Yusliana Yusliana; Mulyadi AR; Lia Hanifa (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
This study aims to determine the financial performance at PT. Mandala Multifinance Tbk from 2019 to 2021. The type of research used is descriptive with a quantitative approach. The data obtained is the financial statements of PT. Mandala Mutifinance Tbk, which is listed on the Indonesia Stock Exchange (BEI) from 2019 to 2021. Quantitative data is data in numerical form. In this study, qualitative data in the form of financial reporting data were obtained from PT. Mandala Multifinance, Tbk is listed on the Indonesia Stock Exchange. Data analysis techniques used to measure financial performance by using the analysis of liquidity ratios, solvency ratios and profitability ratios. The results showed that the financial performance at PT. Mandala Multifinance Tbk is based on a